(untitled) (Acta Scientiarum. Animal Sciences, 2026)
Cattle performance and carcass traits as affected by feedlot pen space allowances were investigated. Bulls (N = 1350) of 30 ± 6 months of age and a weight of 392 ± 46 kg were assigned to one of three pen space allowances: 6 (T6), 12 (T12), and 24 (T24) m2 animal-1. Individual average daily gain (ADG), hot carcass weight (HCW), fat cover (scored from 1 to 5), carcass bruise occurrences, and meat pH24 were assessed. Treatment T24 showed higher (P < 0.05) ADG than T6 and T12. T6 had lower (P < 0.05) HCW than T12 and T24. T6 had the highest percentage of carcasses (P < 0.05) and scored 3 for fat cover, followed by T24 and T12. In all treatments, pH24 was within the acceptable range for good meat quality, ranging from 5.60 (T24) to 5.63 (T6). The mean of new bruises per carcass was lowest for T24 (P < 0.05) and did not differ between T6 and T12 (P > 0.05). Superficial bruises were more frequent in T24 than in T6 and T12 carcasses (P < 0.05). Muscular bruises were higher in T6 than in T12 and T24 (P < 0.05). Based on the results, reduced space in feedlot pens lessens beef cattle performance and downgrades carcass quality.